2019
DOI: 10.1148/radiol.2019190491
|View full text |Cite
|
Sign up to set email alerts
|

MRI Atlas of IDH Wild-Type Supratentorial Glioblastoma: Probabilistic Maps of Phenotype, Management, and Outcomes

Abstract: I socitrate dehydrogenase (IDH) wild-type glioblastoma (World Health Organization grade IV astrocytoma) is the most common malignant primary brain tumor in adults (1). Tumor location is a key parameter in the care of patients with glioblastoma because it correlates with demographic characteristics, clinical presentation, histomolecular characteristics, surgical management, delivery of subsequent oncologic treatments, and, therefore, outcomes (2-6). Improvements in imaging after treatment improves the accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 33 publications
8
40
0
Order By: Relevance
“…Therefore, studies must be conducted based on homogeneous tumor populations with respect to IDH mutational status. This hypothesis was recently supported by Roux et al, who assessed a homogenous IDH wildtype glioblastoma population (n = 392) and found no difference in localization between glioblastoma with and without MGMT methylation, in line with our study (21).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, studies must be conducted based on homogeneous tumor populations with respect to IDH mutational status. This hypothesis was recently supported by Roux et al, who assessed a homogenous IDH wildtype glioblastoma population (n = 392) and found no difference in localization between glioblastoma with and without MGMT methylation, in line with our study (21).…”
Section: Discussionsupporting
confidence: 93%
“…Hence, we pooled the datasets to address this limitation, yielding a more constant and precise range of confidence interval around the hazard ratio, which remained steady around 1 (Figures 2D, F). Our results are in accordance with MRI probabilistic maps of glioblastoma that highlight areas associated with lower survival (15,16).…”
Section: Discussionsupporting
confidence: 89%
“…The present study controlled for patient‐related and methodological biases by selecting a homogeneous population of newly diagnosed supratentorial diffuse gliomas in adults who all underwent the same procedure of MRI‐based, robot‐assisted stereotactic serial biopsy sampling. We used preoperative MRI and early postoperative CT scans obtained as part of the daily clinical practice and we performed imaging normalization and co‐registrations with quality assessments, as previously described 26 …”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the accuracy of the imaging data processing, we assessed the quality of the segmentation and of the spatial normalization by means of visual inspection by two evaluators blind to each other (AR and MZ), as previously reported 26 . In addition, we assessed the quality of the spatial normalization of the actual biopsy trajectory and of the bone‐based biopsy trajectory by superimposing them with surgically induced changes visible on the early postoperative CT scan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation